PERTUMBUHAN, PRODUKSI, DAN VIGOR BENIH PADA BUDIDAYA TUMPANGSARI SORGUM-KEDELAI - Siantar, Parulian Lumban; Pramono, Eko; Hadi, M. Syamsoel; Agustiansyah, A (Journal Galung Tropika, 2019)
Monoculture development of sorghum faces obstacles due to limited land which causes competition in land use with other food crops. Intercropping as a way to overcome land scarcity creates competition between plant species/varieties. This experiment aimed to know effect of varietal combination of sorghum-soybean intercropping on growth, productivity, land equivalence ratio of the croping system. Other than to know the vigor of storability of sorghum seeds. This research was carried out in the farmland of Kuripan Hamlet, Sidodadi Village, Way Lima Subdistrict, Pesawaran District, Lampung Province (5,38° S, 105,03° E) and storage of sorghum seeds was carried out at the Seed and Plant Breeding Laboratory, Faculty of Agriculture, Lampung University, Bandar Lampung, Indonesia from March to December 2018. Single factor experiment with six levels of treatment were applied in a randomized complete block design (RCBD) with 3 replications. The six treatment were varietal combinations of intercropping of Numbu-Grobogan (S1K1), Numbu-Argomulyo (S1K2), UPCA-Grobogan (S2K1), UPCA-Argomulyo (S2K2), Numbu (S1), UPCA (S2), Grobogan (K1) and Argomulyo (K2). The size of the plot was 5 m x 5 m each. The results showed that the cultivation a varietal combination of sorghum-soybean intercropping affected significantly on the plant high, total normal seedling, and strong normal seedlings percentages. The cultivation also affected on seed weight per plant and seed number per plant. The value of land equivalence ratio (LER) this varietal combination intercropping were higger than 1.